1972
DOI: 10.2307/2038067
|View full text |Cite
|
Sign up to set email alerts
|

The Schwarzian Derivative and Univalent Functions

Abstract: Abstract.In this paper we prove under certain conditions the function w=f(z) is univalent in |z| Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 1 publication
(1 reference statement)
1
25
0
Order By: Relevance
“…(3) If we consider m = 1 and α = 1 in Corollary 3.4, the inequalities (3.21) and (3.22) becomes (1.2) and then we obtain the univalence criterion due to Ozaki-Nunokawa [7]. …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…(3) If we consider m = 1 and α = 1 in Corollary 3.4, the inequalities (3.21) and (3.22) becomes (1.2) and then we obtain the univalence criterion due to Ozaki-Nunokawa [7]. …”
Section: Resultsmentioning
confidence: 94%
“…Three of the most important and known univalence criteria for analytic functions defined in the open unit disk were obtained by Nehari [4], OzakiNunokawa [7] and Becker [1]. Some extensions of these three criteria were given by (see [6,9,10,11,12,13] and [14]).…”
Section: Introductionmentioning
confidence: 99%
“…By virtue of a result due to Ozaki and Nunokawa [4], Obradovic et al [3] considered a class of univalent functions.…”
Section: Then F (Z) Is Univalent In Ementioning
confidence: 99%
“…According to a result due to Ozaki and Nunokawa [6], we have the inclusion U(λ) ⊂ S for 0 < λ ≤ 1, and from [3], we also have the inclusion P(2λ) ⊂ U(λ). In [4], the authors have shown that certain results obtained in [3] also hold if P(2λ) is replaced by U(λ).…”
mentioning
confidence: 94%